A man's game : masculinity and the anti-aesthetics of American literary naturalism - Dudley, John, 1965- (Studies in American literary realism and naturalism., 2004)
Demonstrates how concepts of masculinity shaped the aesthetic foundations of literary naturalism. A Man's Game explores the development of American literary naturalism as it relates to definitions of manhood in many of the movement's key texts and the aesthetic goals of writers such as Stephen Crane, Jack London, Frank Norris, Edith Wharton, Charles Chestnutt, and James Weldon Johnson. John Dudley argues that in the climate of the late 19th century, when these authors were penning their major works, literary endeavors were widely viewed as frivolous, the work of ladies for ladies, who comprise.